2008
DOI: 10.1029/2007jd009236
|View full text |Cite
|
Sign up to set email alerts
|

Assessing known pathways for HO2 loss in aqueous atmospheric aerosols: Regional and global impacts on tropospheric oxidants

Abstract: [1] We present a study of the potential importance of known reaction pathways for HO 2 loss in atmospheric aerosols. As a baseline case, we calculate the reaction probability for HO 2 loss by its self-reaction in aqueous particles. Detailed calculations assessed the effects of aerosol pH, temperature, particle size, and aqueous phase diffusion limitations on the rate of HO 2 loss by this process. An algebraic parameterization of the reaction probability, g HO2 , due to self-reaction is valid for aerosol pH < 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
162
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(178 citation statements)
references
References 60 publications
11
162
4
1
Order By: Relevance
“…A range of aerosol uptake coefficients for HO 2 have been reported in the literature, with recent measurements indicating values of γ HO 2 between 0.003 and 0.02 on aqueous aerosols (George et al, 2013), while others have reported values of γ HO 2 ∼ 0.1 (Taketani et al, 2008) and increased uptake coefficients in the presence of Cu and Fe ions (Thornton et al, 2008;Mao et al, 2013). In this work we use a value of γ HO 2 = 0.1 in order to maintain consistency with previous modelling studies at the site and to account for potential impacts of ions of copper and iron in aerosol particles influenced by mineral dust Müller et al, 2010;Fomba et al, 2014;Matthews et al, 2014;Lakey et al, 2015).…”
Section: Constrained Box Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…A range of aerosol uptake coefficients for HO 2 have been reported in the literature, with recent measurements indicating values of γ HO 2 between 0.003 and 0.02 on aqueous aerosols (George et al, 2013), while others have reported values of γ HO 2 ∼ 0.1 (Taketani et al, 2008) and increased uptake coefficients in the presence of Cu and Fe ions (Thornton et al, 2008;Mao et al, 2013). In this work we use a value of γ HO 2 = 0.1 in order to maintain consistency with previous modelling studies at the site and to account for potential impacts of ions of copper and iron in aerosol particles influenced by mineral dust Müller et al, 2010;Fomba et al, 2014;Matthews et al, 2014;Lakey et al, 2015).…”
Section: Constrained Box Modelmentioning
confidence: 99%
“…Treatment of seasalt aerosol is described by Jaegle et al (2011). The uptake coefficient for N 2 O 5 uses the parameterisation by Evans and Jacob (2005), while that for HO 2 uses the parameterisation of Thornton et al (2008). A full description of the organic aerosol chemistry in the model is given by Heald et al (2011).…”
Section: Global Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…At RH relevant to the lower stratosphere (<40%) the measurements showed that γ (HO 2 ) is in the range 0.020-0.028 at 295 K. An inverse temperature dependence of γ (HO 2 ) onto dry seasalt aerosols has previously been observed (Remorov et al, 2002); although there have been no systematic experimental studies of the temperature dependence of γ (HO 2 ), parameterisations have developed (Thornton et al, 2008;Macintyre and Evans, 2011). At stratospherically relevant temperatures (T = 200-220 K), γ (HO 2 ) is likely to be considerably larger than observed at 295 K; however it is not possible to cool the aerosol flow tube/SMPS system to verify this experimentally.…”
Section: Comparison Of γ (Ho 2 ) With Literature Valuesmentioning
confidence: 99%
“…We plan to use the KM-SUB model to further investigate the HO 2 concentration dependence on the HO 2 uptake to aerosols to attempt to elucidate the reaction mechanisms involved. Tables 1 and 2 The HO 2 uptake coefficient obtained at much higher concentrations can be extrapolated to lower HO 2 concentrations using the currently understood aqueous chemistry of HO 2 , as outlined by Thornton et al 48 For conditions that resemble this work for (NH 4 ) 2 SO 4 aerosols, namely 293 K, HO2 = 0.4, [HO 2 ]~10 9 molecule cm -3 and assuming an aerosol pH=5, an extrapolated value  HO2~0 .002 was calculated using Equation (7) in Thornton et al 48 It should be noted that this calculation is extremely sensitive to aerosol pH due to the pH-dependent HO 2 solubility. For example, the calculated uptake coefficient for NaCl aerosols at pH~7 becomes  HO2~0 .12.…”
Section: Dependence Of the Uptake Coefficients Upon Ho 2 Concentrationmentioning
confidence: 99%